Оценка частотной границы допустимого использования приближенных моделей линий передачи при анализе цепей печатных плат - Sirotко, V. K. (PE "Politekhperiodika", Book and Journal Publishers, 2010)
The required frequency border was defined by means of comparison of amplitude signals on receiving end of printed circuit boards transmission lines calculated using more exact electrodynamic models. For the contemporary printed circuit boards materials and designs the frequency border makes 3 GHz.